2022
DOI: 10.35971/jjhsr.v4i1.12208
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Work Stress on Depression and Anxiety Symptoms in Nurses Treating Covid-19 Patients at Royal Prima Rsu

Abstract: Abstrak Berdasarkan World Health Organization (WHO) Covid-19 adalah penyakit menular baru yang disebabkan oleh virus corona. Gejala umumnya adalah demam, kelelahan, batuk, kejang, dan diare. Alasan petugas kesehatan merasa cemas antara lain persyaratan kerja yang tinggi, jam kerja yang panjang saat jumlah pasien meningkat, stigmatisasi masyarakat terhadap petugas kesehatan garda depan membuat dukungan sosial semakin sulit. Dengan tujuan untuk mengetahui bagaimana hubungan dan mengetahui lebih dalam gambaran st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In addition, nurses are often burdened with additional tasks and often carry out activities that are not their functions, for example handling administration, finance and others. The Indonesian National Nurses Association (2007) revealed that as many as 50.9% of Indonesian nurses who work experience work stress, often feel dizzy, tired, unfriendly, and lack rest due to too high workload and inadequate income (2). The results of a survey conducted in France, it was found 74% of nurses experienced stressful events.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, nurses are often burdened with additional tasks and often carry out activities that are not their functions, for example handling administration, finance and others. The Indonesian National Nurses Association (2007) revealed that as many as 50.9% of Indonesian nurses who work experience work stress, often feel dizzy, tired, unfriendly, and lack rest due to too high workload and inadequate income (2). The results of a survey conducted in France, it was found 74% of nurses experienced stressful events.…”
Section: Introductionmentioning
confidence: 99%